(untitled) (Ozone Therapy Global Journal, 2018)
Skin, subcutaneous tissue and underlying muscles wounds are the most common injuries of the clinical routine in veterinary medicine and are usually the results of polytrauma decurrent of car accidents or by attacks by other animals. These wounds require rapid treatment with the aim of decontamination and healing. We have described four cases of wounds in dogs treated topically (bagging, intralesional applications and ozonized oil) and systemically (minor autohemo therapy and intrarectal therapy) with ozone therapy as complementary to the traditional treatment. The wounds had rapid evolution, with decontamination in 2-7 days, an reduction of 40-50% in area between 15-30 days and total healing between 48-60 days. The results of this work propose that the ozone therapy used as adjuvant therapy in the management of wounds is a secure, effective therapy and supports a prompt recovery of the patients.